Assessment of Vascular Change Using Swept-Source Optical Coherence Tomography Angiography: A New Theory Explains Central Visual Loss in Behcet’s Disease - Thanapong Somkijrungroj; Sritatath Vongkulsiri; Wijak Kongwattananon; Peranut Chotcomwongse; Sasivarin Luangpitakchumpol; Korrawan Jaisuekul (Journal of Ophthalmology)
Objective. To evaluate retinal vascular structural change in ocular Behcet’s using optical coherence tomography angiography (OCTA) and fluorescein angiography (FA). Methods. An analytic cross-sectional study of 37 eyes of 21 Behcet’s uveitic patients was performed. Foveal retinal thickness (FRT), perifoveal hypoperfusion areas in superficial capillary plexus (SCP), and deep capillary plexus (DCP) were measured with swept-source optical coherence tomography and OCTA. FA images were used for assessing the vascular features and correlation. Results. Twenty-one patients were enrolled (52.4% males). The average age at onset was 36.7 ± 12.93 years. The median of disease duration was 5 years (1–25). FRT was 118.1 ± 52.35 μm, which correlated with visual acuity (95% CI −60.47, −13.92). Using OCTA, the area of hypoperfusion in SCP (0.47 ± 0.17 mm2) was smaller than that in DCP (1.94 ± 3.87 mm2) (p<0.001). Superficial to deep capillary plexus nonperfusion (SCP : DCP) ratio was 0.57 ± 0.27 which had the positive coefficient correlation with visual acuity (95% CI −0.644, −0.015). Conclusions. OCTA is an alternative noninvasive method to monitor macular ischemia in Behcet. Behcet’s uveitis affects DCP more than SCP. Decreasing SCP : DCP ratio and decrease FRT correlates with poor visual acuity. Macular ischemia and DCP loss can be found early and can explain vision loss in Behcet.